2011
DOI: 10.1063/1.3549266
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of elongated drops in a microfluidic T-junction

Abstract: We present a combined numerical and asymptotic approach for modeling droplets in microchannels. The magnitude of viscous forces relative to the surface tension force is characterized by a capillary number, Ca, which is assumed to be small. The numerical results successfully capture existing asymptotic solutions for the motion of drops in unconfined and confined flows; examples include the analytic Stokes flow solution for a two-dimensional inviscid bubble placed in an unbounded parabolic flow field and asympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
39
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 32 publications
10
39
1
Order By: Relevance
“…Figure 3(a) shows the evolution of neck thickness for both the two-and three-dimensional simulations. In agreement with Leshansky et al (2012), we find that in two dimensions the thickness of the neck decreases monotonically until a grid-dependent collapse (a consequence of the VOF method, see also Afkhami, Leshansky & Renardy 2011). The 3/7 scaling describes the data well, as shown in the inset.…”
Section: Dynamics Of Droplet Breakup In a T-junctionsupporting
confidence: 69%
“…Figure 3(a) shows the evolution of neck thickness for both the two-and three-dimensional simulations. In agreement with Leshansky et al (2012), we find that in two dimensions the thickness of the neck decreases monotonically until a grid-dependent collapse (a consequence of the VOF method, see also Afkhami, Leshansky & Renardy 2011). The 3/7 scaling describes the data well, as shown in the inset.…”
Section: Dynamics Of Droplet Breakup In a T-junctionsupporting
confidence: 69%
“…Although derived for the 2D case, the boundary condition (7) suitably agrees with our 3D simulations and other experimental results [17].…”
Section: Junction Crossingsupporting
confidence: 74%
“…respectively 19 . Similar scaling relations have also been derived for moving foams as well as bubble trains in micro-devices 32 .…”
Section: D Simulations Of Droplet Migration In a Microchannelmentioning
confidence: 99%
“…Numerical simulations which provide a complete description of the flow field can shed light on the present problem. It has been shown that numerical approximations of the Navier-Stokes equations can represent flow physics in many microfluidics applications, such as droplets/bubbles migration and the breakup of droplets at T-junctions [19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%